Automated robotic dispensing technique for surface guidance and bioprinting of cells - Lim, Pei Qi (2019)
This manuscript describes the introduction of cell guidance features followed by the direct delivery of cells to these features in a hydrogel bioink using an automated robotic dispensing system. The particular bioink was selected as it allows cells to sediment towards and sense the features. The dispensing system bioprints viable cells in hydrogel bioinks using a backpressure assisted print head. However, by replacing the print head with a sharpened stylus or scalpel, the dispensing system can also be employed to create topographical cues through surface etching. The stylus movement can be programmed in steps of 10 µm in the X, Y and Z directions. The patterned grooves were able to orientate mesenchymal stem cells, influencing them to adopt an elongated morphology in alignment with the grooves' direction. The patterning could be designed using plotting software in straight lines, concentric circles, and sinusoidal waves. In a subsequent procedure, fibroblasts and mesenchymal stem cells were suspended in a 2% gelatin bioink, for bioprinting in a backpressure driven extrusion printhead. The cell bearing bioink was then printed using the same programmed coordinates used for the etching. The bioprinted cells were able to sense and react to the etched features as demonstrated by their elongated orientation along the direction of the etched grooves.